Sea gravity measurements in the Antarctic regions during the 22nd and 23rd Japanese Antarctic Research Expeditions - Kasuga, Takashi; Fuchinoue, Seiji; Kaminuma, Katsutada; Segawa, Jiro (1983)
P(論文) Sea gravity measurements on board the icebreaker FUJI in the Antarctic regions were conducted in the 23rd Japanese Antarctic Research Expedition (JARE-23). They are the second intensive measurements following the work of JARE-22. Cruise tracks of JARE -22 and -23 have some crossing points in the Antarctic regions. Gravity data at the crossing points were used to calibrate outputs of the sea gravity meter NIPRORI. The icebreaker FUJI entered Amundsen Bay for the first time during the cruise of JARE -23. Detailed sea gravity survey in the bay revealed a significant, local free-air gravity low down to -70 mgal in the area. departmental bulletin paper